Determinarea evoluţiei sărăciei cu ajutorul pragurilor relative ancorate în timp - Pop, Marius Augustin (Calitatea Vieții, 2009)
The events immediately following December 1989 led to a rapid deterioration in the standard of living, especially during phases of marked economic decline. It was normal, under these conditions, to experience several concerns to estimate the welfare deterioration and poverty of the population. Various methods were used along to estimate poverty, of which, the most used was based on monetary absolute and relative thresholds. Each method has also limits and advantages. One method that tries to combine most of the advantages of both, absolute and relative methods could be the relative thresholds anchored in time. The author of article tries to offer a method to build a series of chain base poverty indexes estimated, based on relative thresholds anchored in time, that could be connected to any poverty level and year.